Workers’ Compliance with Covid-19 Prevention and Control Protocols in X Mining Company - Noorleta Putri Rizky; Jaladara Vena; Supriyati Supriyati (BIO Web of Conferences, 2023)
The mining sector presents various risks that can contribute to the spread of Covid-19, such as confined work areas and high worker mobility. The Indonesian government has made several efforts to prevent the spread of Covid-19, including the implementation of health protocols as mitigation measures in workplaces. Employee compliance is a crucial factor in the successful implementation of health protocols in the workplace. The purpose of this study is to analyze the determinant factors of employee compliance in implementing Covid-19 health protocols at Company X. A cross-sectional study was conducted from July to August 2022 with a self-administered questionnaire. The sample of the study was drawn from mining workers in Company X as research subjects. The finding reveals that out of 185 respondents, 91.4% exhibited high compliance in implementing health protocols in the workplace. There is a relationship between knowledge, attitude, company support, vaccination history, and the level of employee compliance in implementing health protocols in the working environment of Company X. This study revealed that company support was the most dominant factor influencing worker compliance. Therefore, good company support is necessary for ensuring employees’ safety and health compliance behavior.